Which Domains of Social Support Better Predict Quality of Life of Women with Breast Cancer? A Cross-Sectional Study - Hadi Zamanian; Mona Daryaafzoon; Sahar Foroozanfar; Zinat Fakhri; Tina Jalali; Amene Ghotbi; Mohammadali Amini-Tehrani (Elsevier, 2021)
Objectives: The study aimed at investigating the specific role of social support types (SSTs) on quality of life (QoL) and its domains of women with breast cancer in Iran. Methods: In this cross-sectional study, a number of 223 women with breast cancer visiting three cancer centers of Tehran, Iran, participated from October 2014 to May 2015. Medical Outcome Study-Social Support Scale and Functional Assessment of Cancer Therapy-Breast Cancer were used for data gathering. Backward multiple regression was utilized, adjusted by age, education, and family size. Results: The study indicated positive correlations between all SSTs and QoL domains, whereas only positive social interaction (PSI) showed a significant association with physical well-being. PSI showed the only predictive performance in terms of all QoL outcomes, beyond the covariates. Conclusions: The study revealed the PSI as the most influential support type to enhance all domains of QoL of women with breast cancer.